Monetary policy and unemployment in open economies - Philipp Engler (Freie Universität Berlin, Fachbereich Wirtschaftswissenschaft, 2011)
After an expansionary monetary policy shock employment increases and unemployment falls. In standard New Keynesian models the fall in aggregate unemployment does not affect employed workers at all. However, Lüchinger, Meier and Stutzer (2010) found that the risk of unemployment negatively affects utility of employed workers: An increases in aggregate unemployment decreases workers' subjective well-being, which can be explained by an increased risk of becoming unemployed. I take account of this effect in an otherwise standard New Keynesian open economy model with unemployment as in Galí (2010) and find two important results with respect to expansionary monetary policy shocks: First, the usual wealth effect in New Keynesian models of a declining labor force, which is at odds with the data as highlighted by Christiano, Trabandt and Walentin (2010), is shut down. Second, the welfare effects of such shocks improve considerably, modifying the standard results of the open economy literature that set off with Obstfeld and Rogoff's (1995) redux model.
Keywords: E24; E52; F32; F41; 330; open economy macroeconomics; monetary policy; unemployment